Quantitative approaches in business studies - Morris, Clare 1948- (Financial Times/Prentice Hall, 2008)
This book gives an introduction to the effective use of mathematical and statistical techniques in business operations, working from first principles and building towards a complete understanding of first-level undergraduate quantitative methods.